2012
DOI: 10.1159/000345353
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling Regulates Intermediate Precursor Production in the Postnatal Dentate Gyrus by Regulating Cxcr4 Expression

Abstract: Previous studies have examined the role of diverse signaling pathways in dentate neurogenesis, but how these signaling pathways are integrated remains unknown. Using mice that allow genetic manipulation of type 1 radial progenitors in the dentate, we show that forced induction of Wnt signaling leads to expansion of the intermediate progenitor cell (IPC) pool while selective activation of Sonic hedgehog (Shh) signaling drives neurogenesis without significant expansion of IPCs. Thus, both Wnt and Shh signaling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 42 publications
2
37
2
Order By: Relevance
“…Previous work from our laboratory showed that Wnt/β-catenin signaling is required for postembryonic hypothalamic neurogenesis , and other studies have also led to the hypothesis that pathway activity promotes radial glial differentiation (Lee et al, 2006;Wang et al, 2011Wang et al, , 2012Choe and Pleasure, 2012;Varela-Nallar and Inestrosa, 2013). By contrast, Wnt/β-catenin signaling has also been shown to promote the self-renewal and expansion of neural stem cells in the mammalian telencephalic subventricular zone and dentate gyrus (Qu et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…Previous work from our laboratory showed that Wnt/β-catenin signaling is required for postembryonic hypothalamic neurogenesis , and other studies have also led to the hypothesis that pathway activity promotes radial glial differentiation (Lee et al, 2006;Wang et al, 2011Wang et al, , 2012Choe and Pleasure, 2012;Varela-Nallar and Inestrosa, 2013). By contrast, Wnt/β-catenin signaling has also been shown to promote the self-renewal and expansion of neural stem cells in the mammalian telencephalic subventricular zone and dentate gyrus (Qu et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…These factors are critical for the maintenance of adult neurogenesis as Shh promotes proliferation of NPCs (Machold et al, 2003) and manipulation of the Wnt pathway nearly abolishes neurogenesis in the adult hippocampus (Lie et al, 2005). It is now known that CXCR4 is a downstream target of Wnt signaling, suggesting that Wnt induces CXCL12-mediated processes in NPCs via receptor regulation (Choe and Pleasure, 2012). …”
Section: Chemokines and Maintenance Of The Adult Cnsmentioning
confidence: 99%
“…In addition, the interactions between the various signaling pathways active within the neurogenic niche must be closely examined. It has been shown that both SHH and WNT3A regulate the NSC population in the perinatal and adult DG through Sox2-dependent autocrine mechanisms (Favaro et al, 2009) and that each may mediate the proliferation and differentiation in different populations of neural progenitors in the DG during early postnatal and adult neurogenesis (Choe and Pleasure, 2012). These nuances in the function of developmental cues need to be carefully considered when taking on the challenge of recapitulating them in the in vitro setting.…”
Section: Hippocampal and Dg Formationmentioning
confidence: 99%